GROWTH AND YIELD RESPONSE OF ARUMBA (Zea mays L. Ceratina) GLUTINOUS CORN VARIETIES TOWARD AMELIORANTS AND GROWTH REGULATORS ON PEATLAND - Railia Karneta; Nurlaili Fitri Gultom; Dewi Meidalima; Nyimas Manisah (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Planting glutinous corn on peatland must be treated using ameliorant ingredients of manure fermented with EM4 and growth regulators. Ameliorated peatland can accelerate the supply of organic and mineral compounds which is easily absorbed by plants so that production can be optimized. This study aims to see the response of ameliorant ingredients and growth regulators on the growth and production of glutinous corn of Arumba (Zea mays L. Ceratina) variety on peatland. This study used a randomized block design (RAK) in factorial consisting of two factors, and three replications. The first factor was the ameliorant material (A), namely A0 = without ameliorant (control), A1 = cow manure fermented with EM4, A2 = chicken manure fermented with EM4, A3 = goat manure fermented with EM4 and he second factor is the type of Growth Regulatory Substance (ZPT), namely Z0 = without ZPT (control), Z1 = Superior Plant Hormone Growth Regulator (Ghost), Z2 = Harmonic Growth Regulatory Substance, Z3 = Atonic Growth Regulator Substance. The variables observed included plant height (cm), stem diameter (cm), weight of wet bean (g), weight of ear (g), length of ear (cm) diameter of ear (cm). The results showed that the ameliorant material from chicken manure fermented with EM4 and the use of superior plant hormone growth regulators (phantoms) provide optimal growth and production of glutinous corn because it corresponds to the description of glutinous corn of the Arumba variety, and is the best treatment.